The Case for Tribunal Standing in Canada - Semple, Noel (2007)
Judicial Review' means a court reviewing a decision made by an administrative tribunal. When judicial review occurs, should the tribunal be allowed to send a lawyer to court to defend its decision? I think it generally should, and this article explains why.
Keywords: Noel Semple